Attachment-related avoidance and the social and agentic content of nostalgic memories. (May 2015) - Abeyta, Andrew A.; Routledge, Clay; Roylance, Christina; Wildschut, Tim; Sedikides, Constantine
The reported research tested whether the social and agentic content of nostalgic memories varies as a function of attachment-related avoidance. We measured individual differences in attachment-related avoidance and anxiety and coded the interpersonal and agentic content of nostalgic and non-nostalgic narratives. Results revealed that nostalgic (relative to non-nostalgic) narratives contained more social content and that this link was not moderated by attachment-related avoidance. There was a significant association between attachment-related avoidance and attachment-related social content in nostalgic, but not non-nostalgic, past narratives. There was also a significant association between attachment-related avoidance and agency content in nostalgic, but not non-nostalgic narratives.